Praktyki pedagogiczne w akademickim kształceniu (przyszłych) nauczycieli wczesnej edukacji - Musiał, Ewa (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The knowledge acquired during the study is a source of projection of one’s own occupational activities, while the professional reality enables a multidimensional application of theory in action which can be the cause of a satisfactory source of reflective practical experience or cause of a sense of helplessness. In addition to the preparation of a substantive nature, practice is an indispensable element of the education system for students.
Keywords: learning in action; professional practice; student education system; teacher of an early education; theoretical knowledge